Influence of window design and environmental variables on the window opening behavior of occupants and energy consumption in residential buildings - Sivapriya Chelliah; Subbaiyan Gnanasambandam; Srinivas Tadepalli (TESEA, Transactions on Energy Systems and Engineering Applications, 2025)
Building energy use, thermal comfort, natural ventilation, and indoor air quality are influenced by the occupant behavior related to the opening and closing of windows in residential buildings. Studies about window opening and closing behaviour focused mainly on environmental variables (indoor temperature and air quality, climatic factors) and contextual parameters (season, time of the day). This paper investigates the influence of factors related to window design and environmental variables on the frequency of opening and closing the windows and the duration of windows in the open position. The impact of window opening behavior on residential energy consumption is also explored in this study. Data related to window characteristics, ease of operation, hours of windows in open/closed state, and frequency of opening and closing the windows are collected through a questionnaire survey from 365 residences. Energy consumption data is obtained from utility bills and weather data from the meteorological department. Among 365 residences, window opening and closing behaviour were monitored in three residences with loggers for a year to validate the data collected through the questionnaire survey. This study reiterated the influence of environmental variables on the windows’ open duration and the frequency of opening and closing the windows. The results reveal that the window characteristics influence the windows’ open duration and the frequency of opening and closing the windows. The study divulged that energy consumption is influenced by the hours the window is in an open state and the frequency of opening and closing the windows.